Entre o Butsudan e a missa: práticas religiosas de imigrantes japoneses no Rio Grande do Sul, Brasil - Tomoko Kimura Gaudioso; André Luis Ramos Soares (Les Cahiers ALHIM)
Despite the current Brazilian Constitution defends religious freedom, Catholicism is the religion of the majority of the population, according to the IBGE survey.  This study aims to show the religious diversity, especially religious expression from the Far East, in particular those that have arisen throughout the Japanese immigration to Rio Grande do Sul, Brazil, Japanese traditional religion, such as Buddhism and Shinto, Japanese new religions, such as Perfect Liberty, Soka Gakkai e Tenrikyô, and the interaction with the local religions, such as Catholicism, Protestantism and African-Brazilian religions. Through survey in the form of interviews, it was found that in addition to dealing with the spirituality aspect of the immigrants, religion has also been used as an instrument of integration between the immigrants and the local society in certain historical moments of the life of these individuals. Our case study shows the different forms of religiosity among the immigrants and how the adoption of different cults does not necessarily means syncretism or multi-religiosity (Kimura e Soares, 2009). The absence of an official religion on Japan does not make the immigrants less religious but with another perception of religiosity, based on the connection between people and their home villages and to the land, in their physical-geographic and supernatural conceptions.